Effects of the longest pause, its location, and pause variance on successful EFL writing performance across writing tasks with diverse degrees of complexity. (November 2022) - Zarrabi, Forooq; Fadavi Amiri, Mohammad Hossein; Bozorgian, Hossein
Abstract: The present research attempts to unveil information about students' cognitive efforts during writing tasks in a foreign language context by exploring (n = 126, mean age: 19.3, SD: 0.47) Iranian EFL (English as a Foreign Language) undergraduate students' pausing behavior across four writing tasks with diverse degrees of complexity. Cognitive efforts have been examined through three process measures (the longest pause, the longest pause location, and the variance indicator). The results indicate that, in general, the longest pause, the longest pause location, and the variance indicators have statistically significant relationships with successful writing performance; nevertheless, our findings show that the associations of the indicators are moderated by task complexity. The three-way interaction effects among the indicators illustrate that they are linked to successful EFL writing performance in an interconnected way.